Generał brygady Jerzy Dobrodzicki (1884–1934) i jego rodzina - Kozłowska, Aleksandra Anna (Przegląd Nauk Historycznych, 2012)
Jerzy Dobrodzicki, born December 14, 1884 in Wadowice, was an Austrian infantry officer, then a brigade general of the Polish Army. In 1905 he joined the Austro-Hungary army. He was a member of the Association for Active Struggle (Związek Walki Czynnej). In 1911 he made contact with the Riflemen’s Associa-tion (Związek Strzelecki) as a combat training instructor. In the World War I he fought on the Russian front as the company and then the battalion commander. In January 1917 he joined the Polnische Wehrmacht. After the „refusal to swear” allegiance to Austria-Hungary and Germany crisis of Polish soldiers in July 1917, J. Dobrodzicki returned to the ranks of the Austrian 20th infantry regiment, which went to the Italian front at the Piava river. He took the lead of the „Freedom” Or-ganisation which coordinated Poles who served in the Austro-Hungary Army. As politically suspect he was pulled from the front to Bochnia near Cracow. After the end of the World War I he was promoted to the rank of major and appointed to organize the 2nd Highlander Riflemen Regiment. During the Polish-Soviet War he commanded the 5th infantry regiment. During the battle of Borodzianka (May 12, 1920) he was seriously wounded and taken to a hospital. During the period November 20, 1920 – September 14, 1921 he commanded the 1st Infantry Brigade. In the years 1921–1926 he was the commander of the 1st Highlander Riflemen Regiment in Nowy Sącz, then the commander of the divisional infantry in the18th Infantry Division in Łomża. In 1929 J. Dobrodzicki was promoted to the rank of brigadier general and appointed commander of the II Corps District (Okręg Korpusu) in Lublin. He died in Warsaw on November 15, 1934 and was buried in Powązki Cemetery. His wife, Zofia Dobrodzicka lived in Warsaw and went through the horror of the Warsaw Uprising in 1944. She died in 1970. During the World War II the general’s only son, Jerzy Andrzej Dobrodzicki, served in the Polish Navy, the branch of the Polish Armed Forces in the West. After the war he lived in Great Britain and moved to Canada in 1949. He died in Ottawa in 2001. His son Andrzej lives with his family Grażyna and Adam in Canada.